Histomorphological and Hormonal Changes in the Testes of Albino Rats Treated with Herbal Aphrodisiac Formular - Wilson, Ajanwachukwu Ogbonna; Ohiwerei Wisdom Omogbai; Olugbenga Mary; Echekwube Marylyn E; Obeagu E I (International Journal of Applied and Scientific Research, 2024)
Herbal supplements, commonly referred to as botanicals, are plant-derived products utilized for their therapeutic properties. This study aims to examine the histomorphological and hormonal changes in the testes of albino rats treated with a herbal aphrodisiac formula. A total of eight male and two female rats were used in the study, with the males divided into control and test groups, while the females were used for mating with the test groups. Group A (Control) received only normal feed (growers’ mash) and distilled water daily for four weeks. Group B was administered 0.2 ml of Men’s Formula supplement and sacrificed on day 7, whereas Group C was administered 0.2 ml of Men’s Formula supplement and sacrificed on day 14. The body weights of the animals were measured before and after acclimatization, and similar weight assessments were performed at the end of each phase, with the average weights recorded accordingly. At the end of the procedure, the testes of each rat were excised under chloroform anesthesia and fixed in 10% formal saline for subsequent histological examination. Blood samples were collected via cardiac puncture into plain bottles, and sera were later separated for hormonal analysis. The results indicated that the herbal aphrodisiac formula enhanced testosterone levels and increased testis weight. However, no significant change (P > 0.05) was observed in body weight, and testicular histology remained unaffected. Further studies with prolonged usage of the herbal aphrodisiac formula are recommended to determine potential long-term effects